Assessing the impact of academic library spaces on users’ behaviour with the ISO16439:2014(E) - Melo, Luiza Baptista; Sanches, Tatiana; Matos, Gaspar; Torres, Patrícia (Qualitative and Quantitative Methods in Libraries; Vol 6 No 3 (2017): September 2017 Issue, 2019)
The importance of library assessment is widely recognized as a useful procedure to better understand and intervene in the reality of these services. In fact, evaluation methodologies seek not only to measure performances and impacts, but also to prepare a sequential action to improve services. This paper presents the research carried out to verify, describe and explain how the spaces of university libraries can affect the behaviour of their users, based on a concrete instrument - ISO 16439:2014(E) standards. Based on a case study of two academic libraries of the Universidade de Lisboa (Faculdade de Medicina Dentária and Faculdade de Psicologia e Instituto de Educação) in which an online questionnaire on these standards is applied, a theoretical reflection is developed based on the concepts of library spaces, in the university context and regarding users’ behaviour towards information.